The Relationship Between Family Support and Self Care in Hypertension Clients - Krisnawati, Nawang Wulan; Abiddin, Andi Hayyun (Health Access Journal, 2024)
Many hypertensive clients get less support from family members. This results in a decrease in the spirit of hypertensive clients in carrying out self-care well, so hypertensive clients are unable to manage signs and symptoms of hypertension and minimize disruption in body function, and complications of hypertension. The purpose of this research is to know the correlation between family support and self-care in hypertension clients in Sumberjo Village Kademangan. The research design used was correlational, with independent variables of family support and dependent variable self-care on hypertensive clients. The data collection techniques used family support questionnaires and self-care questionnaires. The location of the research was conducted in Sumberjo Village Kademangan from 30 June until 03 July 2017. The population was 30 people by using total sampling. The results of family support showed 60 percent good, 20Percent enough, and 20Percent less and selfcare showed 73Percent total self care, 27Percent partial self care. Using the Spearman test shows the value of 0,000 where less than 0,05 meaning there was a correlation between family support with self self-care hypertension clients in Sumberjo Village Kademangan. The correlation coefficient rs is 0.834, which means the correlation of family support with selfcare on hypertension clients in Sumberjo Village Kademangan has a direct correlation. From the results of this study is expected, that health workers to increase cooperation with village officials in providing health services such as counseling. To increase public knowledge about the importance of selfcare for hypertension